PERBEDAAN MEKANISME KOPING MAHASISWA POLTEKKES RS dr.SOEPRAOEN MALANG DALAM MENGHADAPI PROGRAM PENGENALAN KEHIDUPAN KAMPUS ANTARA KELUARGA TNI/POLRI DENGAN BUKAN TNI/POLRI - Priasmoro, Dian Pitaloka (Care : Jurnal Ilmiah Ilmu Kesehatan, 2019)
New students in entering campus life need academic, psychological and social readiness so the need for well-programmed and managed activities is called the Campus Life Introduction Program (P2KK). During this time P2KK often occurs in the form of violations of norms and ethics, and physical violence. This raises various reactions or coping mechanisms. The aim of this study was to analyze the differences in the Koping Student Polytechnic in Taking the Campus Life Introduction Program (P2KK) between Army / Police Families and Non- Army / Police Families.The design in this study is descriptive comparative. The population in this study were all new nursing study program students who underwent P2KK Period totaling 170. The sample in this study was 119 new students who underwent P2KK period which were taken by stratified random sampling. The results of the study showed that almost all respondents of the Army / Police family were 52 people (98.1%). In non- Army / Police families the coping mechanism was entirely adaptive for 66 people (100%). Fisher's test shows p-value of 0.445> 0.05, which means there is no difference in coping mechanisms of the Army / Police family with non- Army / Police. What is possible is influenced by other factors such as cognitive, environment, personality, and social networks. From the results above it is recommended for respondents to always open themselves to the social environment, tell stories and want to ask other people so that they will form a positive personality.